Effectiveness Of Giving Biochar And Poc Tofu Wastewater On The Growth And Production Of Tomato Plants (Solanum Lycopersicum L) - Armaniar; Tharmizi Hakim; Nurjanah Ariska (ISNU Sumatera Utara, 2024)
Tomato plants are one of the most popular fruit vegetables among people. To increase the growth and production of tomato plants, you can use husk charcoal biochar and liquid organic fertilizer from tofu waste. This research aims to determine the effect of providing husk charcoal biochar and tofu water liquid organic fertilizer on the growth and production of tomato plants (Solanum lycopersicum L). This research method uses a Factorial Randomized Block Design (RBD). The first factor is the provision of husk charcoal biochar with the symbol (A), consisting of A0 = 0 kg/plot, A1 = 1 kg/plot, A2 = 2 kg/plot, and A3 = 3 kg/plot. The second factor is the provision of liquid organic fertilizer from tofu waste water (T), consisting of T0 = 0 ml/liter/plot, T1 = 200 ml/liter/plot, T2 = 400 ml/liter/plot, T3 = 600 ml/liter/plot. The results of the study showed that the administration of husk charcoal biochar had a very significant effect on plant height (cm), a significant effect on stem diameter (mm), and a very significant effect on the number of fruit/plants (fruit) , number of fruit/plot (fruit), fruit weight. /plant (g) and fruit weight/lot (g). Where the best treatment is A3 = 3 kg/plot. The application of liquid organic fertilizer from tofu waste water had no significant effect on plant height (cm) and stem diameter (mm), but had a very significant effect on the number of fruit/plants (fruit), number of fruit/plots ( fruit), weight of fruit/plant (g) and weight of fruit/lot (g). Where the best treatment is T3 = 600 ml/liter/plot. The interaction between giving husk charcoal biochar and liquid organic fertilizer from tofu waste water had no significant effect on all observed parameters.